Pemanfaatan Cerpen Kancil dan Buaya Karya Syirli Martin Dalam Pembelajaran Menulis Teks Narasi - Sujana, I Made; Wendra, I Wayan; Artawan, Gde (STKIP AGAMA HINDU SINGARAJA, 2023)
This research aims to describe the use of the short story Kancil and Buaya by Syirli Martin in learning to write narrative texts for class VII D students at SMP Negeri 1 Mengwi. This research uses a qualitative descriptive research design. The subjects of this research were Indonesian language teachers and students of class VII D of SMP Negeri 1 Mengwi. and the objects in this research are the elements contained in the short story Kancil and Buaya by Syirli Martin, the use of the short story Kancil and Buaya by Syirli Martin in learning to write narrative texts, and the student's ability to write narrative texts by utilizing the short story Kancil and Buaya by Syirli Martin in learning to write narrative texts for class VII D students at SMP Negeri 1 Mengwi. The data collection methods used are observation methods and documentation methods. Using qualitative descriptive data analysis techniques with data reduction steps, data presentation, data interpretation, and drawing conclusions. The results of this research are that there are intrinsic elements consisting of theme, plot, characters, setting, language style, message, and point of view. The use of the short story Kancil and Buaya by Syirli Martin in learning to write narrative texts was used as media and material in learning and students' ability to write narrative texts obtained a class average score of 79 in the good category.